Sa duyan ng sining - Go, Johnny; Mangilog, Pauline (Quezon City Jesuit Communications, 2000)
A documentary featuring five prominent contemporary Filipino artists, discussing in interviews their lives and their art.
VHS.
Keywords: Music; Visual art; Film